Status of animal welfare implementation by standard of Office International des Epizooties (OIE) on dairy cow in East Java Indonesia - kristanti, novita dewi; Rawendra, Rudy; Wahyudi, Andri Tri (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
Animal welfare is life quality aspect of animal that relates to physical and psychological condition, as well as environment where the animals live. Statistically, populations of the dairy cows in East Java in 2017 were 273.881. Objective of the research was to study implementation of animal welfare on dairy cows in East Java. Survey was conducted from May to June 2020. Instruments used in this research were standard Office International des Epizooties (OIE) on Terrestrial Health Code 7.11 that comprised of 8 aspects: behavior, morbidity, mortality and culling, the change of weight; body condition; and dairy production, reproductive efficiency, physical appearance, response of handling, and complication post general procedure. Result for the application of animal welfare using standard Office International des Epizooties on Dairy Cow in East Java was categorized adequate/sufficient by percentage 70.73%. Among 29 indicators of measurement, 1 indicator belongs to the least category. The category showed that an area for exercise with average score was 1.38 (27.57%).